PENGARUH GOOD CORPORATE GOVERNANCE, LEVERAGE DAN CORPORATE SOCIAL RESPONCIBILITY TERHADAP KINERJA KEUANGAN (STUDI KASUS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI PERIODE 2010-2013) - Wuryanti K; Siti Khotimah (Department of Management, Faculty of Economics, Universitas Islam Sutan Agung, Semarang, 2015)
This study aims to examine and analyze the role of Corporate Social Responsibility (CSR) as an intervening variable in mediating the effects of Good Corporate Governance and Leverage for Financial Performance.Samples are 132 companies went public and consists of several industry listed in Indonesia Stock Exchange 2010-2013. Sampling using purposive sampling technique that is based on the completeness of the annual report of each period studied and the conditionsthat have been determined by researchers. To test the hypothesis using linear regression analysis barganda (Multiple Linear Regression) with the application of SPSS version 20.Based on the resultsof data analysisshowedthat theLeverageandCorporateSocial Responsibility (CSR) simultaneously significant effect onfinancial performance. PartiallyGCGsignificant effect onCorporateSocial Responsibility(CSR), whilegood corporate governancedoes not affect thefinancial performance, andLeverageno significant effect onCorporateSocial Responsibility(CSR). VariableCorporate SocialResponsibility (CSR) can becomean intervening variablein mediating theeffects ofGood Corporate GovernanceforFinancial Performance. However,CorporateSocial Responsibility(CSR) was notable tobecomean intervening variablein mediating theeffect ofleverageon financial performance.Keywords: GCG, Leverage, CSRandFinancial Performance.